’n Inleidende bespreking oor die aard en gesag van die binding aan die belydenisskrifte - A. le R. du Plooy (In die Skriflig, 1991)
The Synod of Dordrecht (1618/19) decided on a Form of Subscription which contains a declaration of agreement. The divergent opinions and controversies with regard to the character and authority of this agreement are discussed in this article. The author investigates the purpose and the significance of the signing of the Form of Subscription. In contrast to the historico-critical approach, the dose relationship between Scripture and Confession is emphasized, as well as the authority of Scripture and the authority of the creeds (quia, not qualenus). The conclusion arrived at is that the signing of the Form of Subscription should never become a mere form or a traditional performance.